Analysis and Dynamic Load Characteristic Modeling of RV Reducer - Liu Xueao; Xu Honghai (Jixie chuandong)
The RV reducer is the key component of industrial robots,and the dynamic characteristic is the core problem of its structure design. As the characteristics of the complicated structure of RV reducer and the difficulty in theory modeling,based on virtual prototype technology,the dynamics model of RV reducer is established by using Pro / E parametric modeling and ADAMS software. With the pin gear and cycloidal gear meshing force as the goal,the influence rule of the design parameters on meshing force is analyzed. The results show that with the number of cycloidal gear tooth,the short amplitude coefficient and the pin gear center distribution circle radius increase,the meshing force decreases. The relationship between meshing force and pin gear radius is nonlinear. And the number of cycloidal gear tooth,the short amplitude coefficient and the pin gear center distribution circle radius are the main factor affecting the meshing force,the effect of pin gear radius is relatively small. The influence of each parameters on RV transmission is also analyzed. The result is important to the design of RV reducer.